Flame retardancy and thermal and mechanical performance of intercalated, layered double hydroxide composites of polyamide 11, aluminum phosphinate, and sulfamic acid. Issue 20 (5th February 2016) - Zhang, Sheng; Tang, Wufei; Gu, Xiaoyu; Jiang, Peng; Sun, Jun; Sophie, Duquesne; Bourbigot, Serge; Casetta, Mathilde
ABSTRACT: Sulfamic acid‐intercalated MgAl‐layered double hydroxide (SA‐LDH) was prepared and added with aluminum phosphinate (AlPi) into polyamide 11 (PA11). The results showed that AlPi/SA‐LDH made a positive contribution to both flame retardancy and thermostability, and the effect was demonstrated with the limiting oxygen index (LOI), vertical burning tests (UL‐94), cone calorimetry (CONE), and thermogravimetric analysis (TGA). The char morphologies were observed by SEM, and its chemical composition was investigated by Fourier transform infrared spectroscopy (FTIR). The decomposition mechanism was examined by TGA‐FTIR. The results showed that the LOI of PA11 was only 23.0 and cannot pass any UL‐94 rating. The addition of 20% AlPi increased the LOI to 31.5 and passed the UL‐94 V‐1 rating, and AlPi/SA‐LDH 15%/5% increased the LOI to 32.4 and also passed the UL‐94 V‐1 rating. The CONE results revealed that 20% of either AlPi or AlPi/SA‐LDH brought about a 30% decrease in the peak heat release rate (pHRR). The contribution of SA‐LDH to flame behavior was especially reflected in the postponement of pHRR. SEM showed that the char morphologies became denser after SA‐LDH incorporation. The improvement in thermal stability of the AlPi/SA‐LDH combination was documented by TGA in both N2 and air atmospheres. The mechanical performance deterioration caused by AlPi was partly improved by SA‐LDH. The storage modulus ( E′ ) below the Tg of AlPi/SA‐LDH 15%/5% was about 300 MPa higher than with 20% AlPi. This was attributed to a compatibility improvement. The interaction forces among PA11, AlPi, and SA‐LDH were probed by X‐ray photoelectron spectrometry. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43370. Abstract :